Validating Scope Design in Project STTF Case Study PT.XYZ - Agustian Mauludin; Wawan Tripiawan; Achmad Fuad Bay (School of Industrial and System Engineering, Telkom University, 2020)
PT.XYZ is a company in the Telecommunication Industry. Due to increase the product sales, PT.XYZ performed an annual project to build network infrastructure to the uncovered network areas, called the STTF project. As a project owner, conducting a high performance of scope validation is very crucial to make sure the quality of the result meets requirements. However, the previous project result has shown to the unsatisfactory result, i.e. titled pole resulting in high cable attenuation and over budget. To see the extent of the performance and effectiveness of the validation process, an evaluation of the current validate scope process is necessary. One of the methods is by comparing the operational implementation in the current STTF project against the project management standard to ensure the process performed effectively. Data collected using a questionnaire based on PMBOK 6th ed. standard processes using a self-assessment survey, and two project locations are chosen as a comparative sample. The verified questionnaires then distributed purposively to validate the scope team. In the end, the result of the research shows the implementation of validate scope activity is not comply with the standard process in PT.XYZ and there are gaps against standard practices in PMBOK.